Small farmers' preferences for weather index insurance: Insights from Kenya - Kenneth W. Sibiko; Prakashan C. Veettil; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Smallholder farmers in developing countries are particularly vulnerable to climate shocks but often lack access to insurance. Weather index insurance (WII) is a promising innovation, but uptake has been lower than expected. WII contracts are not yet sufficiently tailored to the needs and preferences of smallholders. We combine survey and choice-experimental data from Kenya to analyze an existing WII program and how changes in contractual design might encourage uptake. Better training, higher levels of transparency, and offering contracts to small groups rather than individual farmers would increase willingness to pay. Basis risk does not seem to be a major constraint.
Keywords: D81; O17; Q12; Q13; 330; climate risk; smallholder farmers; crop insurance; discrete choice experiment; Africa